Biologics and small molecule inhibitors for hidradenitis suppurativa. Issue 2 (18th January 2022) - Shih, Terri; De, Devea R.; Shi, Vivian Y.; Hsiao, Jennifer L.
Abstract: Background: Hidradenitis suppurativa (HS) is a debilitating, chronic inflammatory dermatosis that is often recalcitrant to first‐line treatments. Though mechanisms underlying its pathology remain unclear, a number of upregulated inflammatory cytokines (including tumor necrosis factor‐α [TNF‐α], interleukin [IL]‐1, IL‐17, IL‐12, and IL‐23) have been identified in HS, leading to a growing investigation of targeted biologic therapies in moderate‐to‐severe HS. Objective: We aim to review the current literature on biologics and small molecule inhibitors that have been used to treat HS and discuss mechanisms of action, dosing, safety considerations, and recommendations for use. Findings: Biologics that have been reported to treat HS include TNF‐α inhibitors (adalimumab, infliximab, golimumab, and certolizumab), IL‐1 inhibitors (anakinra and canakinumab), IL‐12/23 inhibitor (ustekinumab), IL‐23 inhibitors (guselkumab, risankizumab, and tildrakizumab), IL‐17 inhibitors (secukinumab, ixekizumab, and brodalumab), and small molecule inhibitors (tofacitinib and sirolimus). Though adalimumab is currently the only FDA‐approved agent to treat HS, those who do not have an optimal response may still benefit from a different anti‐TNF agent, particularly high dose infliximab. A number of other targeted treatments have also shown promising results in small prospective studies for consideration in HS patients. Additional considerations in biologic therapy include mitigating patient concerns about injection reactions and choosing agents that may also treat comorbid conditions. Conclusion: This review summarizes the current literature on the use of biologics and small molecule inhibitors in HS. There remains a significant and continued need to expand the treatment armamentarium for moderate to severe HS